American government institutions & policies : the essentials - Wilson, James Q.; DiIulio, John J.; Bose, Meenekshi (Wadsworth Cengage Learning, 2013)
Acclaimed for the scholarship of its prominent authors and the clarity of its narrative, AMERICAN GOVERNMENT: THE ESSENTIALS sets the standard for covering the historical development of the American political system and its institutions and policies.